2021
DOI: 10.1016/j.sjbs.2021.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization, antidiabetic and anticancer activities of Santolina chamaecyparissus

Abstract: Santolina chamaecyparissus is an important medicinal plant growing in the Mediterranean region and has been reported as a potent anti-inflammatory, antibacterial, antioxidant, and antifungal agent. The purpose of the current research is to identify the chemical constituents in ethyl acetate extract (EAE) from the leaves of S. chamaecyparissus , and to evaluate antidiabetic, and anticancer activity. Chemical constituents of EAE were identified by GC-MS, and the antidiabetic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 28 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…Yen et al [51] also validated the in vitro antidiabetic effect of the oils produced by medicinal plants. The constituents present in the mentioned screening are also present in S. edelbergii such as thymol which acts as an antidiabetic agent described by Escobar et al [40] and 2-methylhexacosane reported by Ali et al [52]. The data documented from our results agree with the literature available for S. orientalis and S. articulata listed by Formisano et al [53]-since the selected species belong to the same genus.…”
Section: In Vitro Antidiabetic Assaysupporting
confidence: 90%
“…Yen et al [51] also validated the in vitro antidiabetic effect of the oils produced by medicinal plants. The constituents present in the mentioned screening are also present in S. edelbergii such as thymol which acts as an antidiabetic agent described by Escobar et al [40] and 2-methylhexacosane reported by Ali et al [52]. The data documented from our results agree with the literature available for S. orientalis and S. articulata listed by Formisano et al [53]-since the selected species belong to the same genus.…”
Section: In Vitro Antidiabetic Assaysupporting
confidence: 90%
“…It was recently found that tetraethylene glycol exerts anticancer effects against Jurkat, K562, HEK293, HeLa, and U937 cell lines ( D’yakonov et al, 2021 ). 1-pentadecane was also recently reported to be present in ethyl acetate extract of S. chamaecyparissus which showed antidiabetic and anticancer efficacy against human breast cancer MCF-7 cells ( Ali et al, 2021 ). 1-pentadecane was also reported to be present in Streptomyces malaysiense sp.…”
Section: Discussionmentioning
confidence: 98%
“… Compound name Molecular formula Nature Biological activity Reference 1 Hexadecane, 2,6,11,15- Tetramethyl C 20 H 42 Hydrocarbon Flavoring agent Pammi et al, (2021) 2 Octacosane C 28 H 58 Hydrocarbon Antimicrobial activity, Insecticidal activity Khatua et al, (2016) 3 Dodecanoic Acid, 1,2,3- Propane -triyl ester C 39 H 74 O 6 Fatty acid hepatoprtective. b5-α reductase inhibitor, Flavour, Lubricant, Hypocholesterolemic, Cosmetic, Achi and Ohaeri, (2015) 4 Hexatriacontane C 36 H 74 Hydrocarbon Antibacterial, antiviral, anticancer Ibnouf, (2021) 5 Heptacosane C 27 H 56 Hydrocarbon Anti-oxidant activity, Antibacterial, Insecticidal Khatua et al, (2016) 6 Eicosyl Acetate C 22 H 44 O 2 Fatty acid Anti-cancer Ali et al, (2021) 7 Tritetracontane C 43 H 88 Hydrocarbon For treating wounds, ulcers, burns, scars and keloids Ibnouf, (2021) 8 Tetracosane, 2,6,10,15,19,23-Hexamethyl C 30 H 62 Hydrocarbon Pesticide, Chemopreventive, Immunostimulant, Cancer preventive, Antitumor, Antioxidant, Antibacterial, Sudha et al, (2013) 9 Myristic Acid vinyl ester C 16 H 30 O 2 Fatty acid Antimicrobial, anticancer, cosmetics …”
Section: Resultsmentioning
confidence: 99%